CONSCIOUS CONSUMPTION AND SUSTAINABILITY: : REFLECTION IN LIGHT OF THE PRINCIPLE OF FRATERNITY - Victória Guanabara Moura, Lara (Revista Gênero e Interdisciplinaridade, 2022)
The unconscious intake of beef affects environmental preservation negatively, thus, this scientific article has as its objective to highlight - by means of doctrinaire researches, ratifying the deductive methodology - how certain eating habits encouraged to society, since the beginning of our existence, postpones environmental preservation. In other terms, it demonstrates how the reduction of beef consumption, above all, can benefit the relationship between human beings and nature and ratify the fundamental right to a healthy environment, which is a third-dimensional right. At first, the grievous impacts caused to nature due to the production and consumption of beef were analyzed. In this perspective, conscious consumption is also verified considering the consumer society in which we are inserted, as well as a close observation in how education has an essential role in consumers’ process of awareness, a fact that leads to the objectification of the principle of fraternity guaranteed by the Magna Carta. The theme of this article is not numerous in terms of research, that is, a little explored theme in face of scientific analyses. Moreover, it is meaningful to emphasize the originality and importance of the scientific article, as there is an urgent need for alternatives that can effectively reduce the environmental impact caused by today’s society, and for this, it is essential to know the causes of the negative effects originated from excessive consumption.